Fertility preservation for patients affected by endometriosis should ideally be carried out before surgery. Issue 5 (November 2021) - Santulli, Pietro; Bourdon, Mathilde; Koutchinsky, Sonia; Maignien, Chloé; Marcellin, Louis; Maitrot-Mantelet, Lorraine; Pocate Cheriet, Khaled; Patrat, Catherine; Chapron, Charles
Abstract: Research question: What prognostic factors relate to a high oocyte yield in fertility preservation for women affected by endometriosis? Design: Observational cohort study conducted in a tertiary care university hospital between April 2015 and January 2019. Women who had undergone fertility preservation with ovarian stimulation for oocytes and embryo vitrification for endometriosis were included. Prognostic factors associated with the number of oocytes retrieved after the first ovarian stimulation were analysed. Results: A total of 146 women who had undergone 258 ovarian stimulation cycles were included; 82 (56.2%) had undergone more than one ovarian stimulation cycle; 72.6% had at least one endometrioma lesion; and 36.3% had previously undergone surgery for endometriosis. After adjustment by multiple linear regression, the factors that significantly reduced the number of oocytes retrieved were previous history of surgery for ovarian endometriosis (coefficient –1.08; 95% CI –2.02 to –0.15; P = 0.024); women's age (–0.21; 95% CI –0.41 to –0.01; P = 0.039); and total dose of gonadotrophin used (–0.01; 95% CI –0.01 to –0.00; P = 0.047). Anti-Müllerian hormone serum level and gravidity positively correlated with an increase in the number of oocytes retrieved (1.65; 95% CI 1.13 to 2.17; P < 0.001 and 3.30; 95% CI 0.91 to 5.68; P = 0.007, respectively) after the first ovarian stimulation cycle. Conclusion: A history of surgery for ovarian endometriosis was associated with significantly lower oocyte yields. Fertility preservation should be integrated into endometriosis management. Fertility preservation should ideally be made available to the patient before surgery.